Design and Implementation of Android-Based Public Transport Trayek using Cloud Computing Infrastructure - Nugroho, Okvi; Ardi Hutagalung, Gabriel (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
Transportation Route System is a system that was built to improve and to meet the needs of public transport users with technology at the present time. the purpose of making the transportation route system is to facilitate the public so that it can create facilities when searching for the desired transportation. The transportation route system uses SDLC (system Development Life Cycle) technology in building it so that the system is made more neat and complex. Google maps technology becomes the main thing on the transportation route system because Google Maps will show the route when the transportation is running. Keyword : Transportation, SDLC, Google Maps.